2024
DOI: 10.1039/d3cc05581g
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy modulated Fe-doped Co3O4 hollow nanosheet arrays for efficient oxygen evolution reaction

Qianyun He,
Lei Han,
Kai Tao

Abstract: Herein, Fe-doped Co3O4 hollow nanosheet arrays with rich oxygen vacancies (Vo-Fe-Co3O4) are constructed through a facile stratedy. Benefiting from the compositional and structural superiorities, the Vo-Fe-Co3O4 exhibits a remarkable OER...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…3(d) to be 782.3 eV and 797.6 eV, respectively. 35–37 As can be seen from Fig. 3(e), the peaks of S 2p at 162.7 eV and 163.8 eV are attributed to S 2p 3/2 and S 2p 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 82%
“…3(d) to be 782.3 eV and 797.6 eV, respectively. 35–37 As can be seen from Fig. 3(e), the peaks of S 2p at 162.7 eV and 163.8 eV are attributed to S 2p 3/2 and S 2p 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 82%
“…For instance, Tao et al engineered an advanced OER electrocatalyst by incorporating oxygen defects and iron doping into Co 3 O 4 . 12 Analysis of Nyquist plots revealed that the oxygen-deficient and Fe-doped Co 3 O 4 (V o -Fe-Co 3 O 4 ) exhibited the lowest charge-transfer resistance ( R ct ) of 2.3 Ω, significantly lower than Fe-doped Co 3 O 4 without oxygen defects (3.6 Ω) and undoped Co 3 O 4 (6.98 Ω), highlighting the role of oxygen defects in improving conductivity.…”
Section: Roles Of Defects In the Oermentioning
confidence: 98%
“…Up to now, NaBH 4 reducing treatment has been widely used to create defects in V O -Fe-Co 3 O 4 , V O -NiCo 2 O 4 , V O -Co 3 S 4 /CeO 2 , V O -NiFe LDH, V S -Co 3 S 4 /MoS 2 , and V S -Co 3 S 4 /rGO. 10,12,78–81…”
Section: Fabrication Strategies For Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further optimization of the electrochemical performance can be achieved by tuning the compositions, defects, and morphologies of the electrode materials. 77,78…”
Section: Various Mof-derived Ldhs For Supercapacitorsmentioning
confidence: 99%